Simulation and Experimental Study on a New Successive Forming Process for Large Modulus Gears - Yao Lin (SpringerOpen, 2021)
Abstract A successive tooth forming process for producing large modulus spur gears (m>2.5 mm) is firstly proposed in this paper to break the restrictions of large forming load and large equipment structure of traditional plastic forming. It contains the preforming stage and the finishing stage. In the first stage, the die with a single-tooth preforms gear teeth one by one through several passes. In the second stage, the other die with multi-teeth refines the preformed teeth into required shape. The influence of total pressing depth and feed distribution in preforming stage on final forming quality is analyzed by numerical simulation, and the reasonable process parameters are presented. Successive tooth forming experiments are carried out on the self-designed gear forming device to verify the optimal simulation results. Gears without fold defects are well formed both in simulations and experiments, proving the feasibility of this method. Compared with the whole die forging process, the new technology has advantages of smaller load and simpler tooling, which shows a good potential for manufacturing large modulus and large size spur gears.